2015
DOI: 10.1016/j.combustflame.2015.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Engine Combustion Network (ECN): Global sensitivity analysis of Spray A for different combustion vessels

Abstract: a b s t r a c tGlobal sensitivity analysis was conducted on Spray A of the Engine Combustion Network's (ECN) experimental conditions across different combustion vessels from different institutions. The main objective was to understand the influence of differences in boundary conditions on specific targets of interest. A list of experimental initial, boundary, and injection conditions with uncertainty ranges were identified for three different ambient conditions for these combustion vessels. Five targets includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…The spray experiments presented in this work were performed in a constant volume pre-burn chamber, which has provided a platform for model development and validation at engine relevant conditions [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. A detailed description of the experimental setup and measurement procedures can be found in the literature [28][29][30].…”
Section: Experimental Datamentioning
confidence: 99%
“…The spray experiments presented in this work were performed in a constant volume pre-burn chamber, which has provided a platform for model development and validation at engine relevant conditions [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. A detailed description of the experimental setup and measurement procedures can be found in the literature [28][29][30].…”
Section: Experimental Datamentioning
confidence: 99%
“…Pickett et al [9] and Meijer et al [14] reviewed the Spray A experiments in different high-temperature and high-pressure facilities in the ECN community. Some computational studies to investigate Spray A have also recently been reported [15][16][17][18][19][20][21][22][23][24][25][26][27], for example, using RANS-based transported probability density function (TPDF) method [15,23,26] and flamelet-type models [16][17][18] to demonstrate the importance of the effect of turbulence-chemistry-interaction (TCI) at diesel-engine conditions, and using large eddy simulation (LES)-type models [19-22, 24, 25] to demonstrate the capability of LES of simulating diesel spray.…”
Section: Introductionmentioning
confidence: 99%
“…Another experimental facility used in generating data for development of chemical kinetic models and computational fluid dynamic (CFD) simulations is a constant volume combustion chamber (CVCC) [13][14][15][16][17]. This is a high-pressure facility used for generating data for the Engine Combustion Network (ECN) [18][19][20], a library containing diesel spray experiments at various engine-relevant operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The two-stage Lagrangian model (TSL) employed in this study describes mixing as a two-stage process that is seen in a frame moving downstream with the normal fluid motion. The model is capable of adopting detailed chemical kinetics while also simulating basic mixing process that are important in turbulent gaseous-jet diffusion flames [18,19,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%